Evaluation of the relationship between neutrophil-to-lymphocyte ratio and 25-hydroxy vitamin D levels in hemodialysis patients, Isfahan, Iran - Azar Baradaran; Zahra Hoseini; Parin Hedayati; Reyhaneh Shirvani (Journal of Preventive Epidemiology, 2021)
Introduction: Chronic low-grade inflammation is a comorbid factor in Chronic kidney disease (CKD), and especially in chronic dialysis patients. Recently, neutrophil-to-lymphocyte ratio (NLR), which is very available and affordable, has emerged as an inflammatory index in many disorders such as CKD. Several studies also have shown the anti-inflammatory effects of vitamin D, and scientists believe that we must prevent vitamin D deficiency in CKD patients. Vitamin D supplementation may decrease mortality and morbidity in end-stage renal disease (ESRD) patients. Objectives: There are few studies on the association between serum 25-hydroxy vitamin D levels and NLR in ESRD patients. Therefore, we tried to evaluate this correlation, hoping to be a key for more researches. Patients and Methods: We enrolled 140 ESRD hemodialysis patients in a cross-sectional study and evaluated the correlation of NLR with serum 25-hydroxy vitamin D levels and some demographic factors in these patients. Results: Our results showed a statistically significant negative correlation between NLR and serum 25-hydroxy vitamin D levels (P=0.010, r= -0.216). However, other variables such as disease duration and age had no correlation with NLR (P=0.649, r= - 0.039 and P=0.781, r= - 0.024, respectively). We also used a linear regression test to check any confounder associated with NLR, and the regression was only significant for serum 25-hydroxy vitamin D levels (P=0.011, B=-0.009). Conclusion: Based on the results, serum 25-hydroxy vitamin D levels can be considered a predictor for NLR in hemodialysis patients.